Community Empowerment through Entrepreneurship and Financial Management Training for SMEs - Muzayyanah Yuliasih; Lia Nurina; Wahyu Purwandari; Rina Destiana; Muh. Zulfi Qadri (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2024)
The community service program titled "Empowering Communities through Entrepreneurship and Financial Management Training" was conducted in Batuampar Village, Kramat Jati District, DKI Jakarta, focusing on small and medium enterprises (SMEs). This program aimed to enhance the capacity and skills of the community in managing businesses more effectively and efficiently through entrepreneurship and financial management training. The implementation method involved material presentations and guided group discussions (Focus Group Discussions) to facilitate active participation from the participants. The training results showed a significant increase in participants' understanding of business strategies, financial management, and the use of digital technology. Before the training, only 35% of participants understood business strategies, and this number increased to 80% after the training. The participants' satisfaction with the training reached 90%, indicating that the approach used was effective in enhancing participant engagement and enthusiasm. Additionally, the training successfully improved networking and collaboration among participants, which was previously only 25% and increased to 70%. This program positively contributed to local economic empowerment and demonstrated potential for further development to support the sustainability of SMEs in the area.